Dirección estratégica de la Institución Educactiva Privada "Mentes Brillantes - San Isidro" y su contribución al desarrollo educativo de la Región La Libertad. - Benites Hidalgo, Carlos Alejandro (2014)
This research study entitled "Strategic Management of School Private" Brilliant Minds - San Isidro "and their contribution to the educational development of the region La Libertad" was held because at present the educational institutions do not provide the level of education is required and that is reflected in recent international reports such as PISA (Programme for International Student assessment) that Peru ranked last among 65 countries. Therefore, the Private School "Brilliant Minds - San Isidro" poses a strategic management model (which is described in the attachments section at the end of the thesis) that is beginning to contribute to the educational development of the Region La Libertad. Inductive, analytic - synthetic deductive: For this study, the descriptive research design, and the following methods were used. The study was performed with historical data and information provided by the company and the interview with the manager and surveys of teachers, students and parents of the institution. With this research it is concluded that the Strategic Management of School Private "Brilliant Minds - San Isidro" is contributing to the educational development of the region La Libertad as approaches requiring UNESCO and can be reflected in the polls.